Leukocyte count and neutrophil-lymphocyte ratio in the second trimester of pregnancy as a predictor of preeclampsia - Reyna-Villasmil, Eduardo (2022)
Objective: To establish the usefulness of leukocyte count and neutrophil/lymphocyte ratio in the second trimester of pregnancy as a predictor of the development of preeclampsia. Design: Case-control study. Institution: Hospital Central "Dr. Urquinaona", Venezuela. Participants: Pregnant women between 17 and 20 weeks who attended prenatal consultation and were followed up to term. Methods: Blood samples were taken from the pregnant women who were followed until delivery to establish whether they developed preeclampsia. Main outcome measures: General characteristics of the patients, values of leukocytes, neutrophils, lymphocytes, neutrophil/lymphocyte ratio and prognostic efficacy. Results: Of the 504 patients selected, 41 pregnant women developed preeclampsia (group A) and 463 pregnant women were considered as controls (group B). No statistically significant differences were found in overall characteristics at baseline (p = ns). The gestational age at the time of diagnosis of preeclampsia in group A was 35.0 +/- 3.2 weeks. Patients in group A were found to have significantly higher values of leukocytes, neutrophils and neutrophil/lymphocyte ratio along with lower values of lymphocytes compared to patients in group B (p < 0.05). Only the absolute values of neutrophils (area under the curve 0.810) and neutrophil/lymphocyte ratio (area under the curve 0.963) had useful prognostic values for discriminating between patient groups for the development of preeclampsia (p < 0.05). Conclusion: The neutrophil/lymphocyte ratio and absolute neutrophil count in the second trimester of pregnancy are useful tools in the prediction of preeclampsia.